The Problem of Scattering by a Mixture of Cracks and Obstacles. (30th November 2009) - Yan, Guozheng
Abstract : Consider the scattering of an electromagnetic time-harmonic plane wave by an infinite cylinder having an open crackΓ and a bounded domainD inR 2 as cross section. We assume that the crackΓ is divided into two parts, and one of the two parts is (possibly) coated on one side by a material with surface impedanceλ . Different boundary conditions are given onΓ and∂ D . Applying potential theory, the problem can be reformulated as a boundary integral system. We obtain the existence and uniqueness of a solution to the system by using Fredholm theory.